Lagos peri-urban housing developments and management: challenges and planning intervention / Funmilayo Mokunfayo Adedire and Mike Adebamowo. - Adedire, Funmilayo Mokunfayo; Mike, Adebamowo (Faculty of Architecture, Planning and Surveying Universiti Teknologi MARA, 2018)
The aim of this study is to assess the existing challenges in the management of Lagos peri-urban and the intervention measures put in place by the regional government. Using case study approach and twostage sampling techniques, the sample size constitutes heads of 370 housing units selected randomly from clusters of purposively selected 16 settlements in Ibeju-Lekki peri-urban. Purpose sampling was adopted to minimise cost because the settlements were dispersed over a wide geographical area. The Primary sources of data were structured interview and questionnaires administered through field survey to planning personnel and selected household heads respectively. Data analysis was done by using descriptive statistics. Findings show three levels of challenges as environmental, socio-economic and institutional. Notable among the challenges were flooding, industrial pollution, traffic congestion, rising cost of commodities, unaffordable land, lack of social facilities, land regularisation, inadequate land data and land speculation. Measures put in place to counter challenges include zoning, and effective town planning policy and management. It is recommended that the regional government should design a policy that would guide in managing the spatial pattern of growth and infrastructure distribution in Lagos peri-urban settlements. Also, this study should be conducted in other peri-urban settlements in developing countries.